Effect of Employee Participation on Organizational Performance in Manufacturing Firm (A Study of Dufil Prima Food Plc, Ogun State, Nigeria) - Ejiro G. UKPEIBO; Uwalomwa UWUIGBE; Edu J. USENDIAH; Somto J. OKOLO (Communications of International Proceedings, 2022)
The study  focus  is on the effect of employee participation in organisational performance. Employees of the chosen organisation (Dufil Prima Food Plc) in Ogun state made up the study's population. To obtain data from the sampled respondents, this study used a purposive and convenience sampling technique. The study's sample size was given as 380. Only 180 of the 195 questionnaire given to the participant were returned, with 25 remaining were not returned. Tables were used to examine the data, which was also used to test the research hypotheses. The major data collection instrument was a Google online form questionnaire, and the study instrument's validity and reliability were confirmed. The data acquired for this study was analyzed and presented by adopting the use of descriptive and inferential statistics. From the findings, employee participation has a positive significant effect and a very strong relationship on organisational performance in Dufil Prima Food Plc, Ogun State. The study concluded that employee participation had a positive significant effect on organizational productivity. Employees should be permitted to contribute to policy formation since they play a big role in policy implementation, and this, among other things, will boost organizational efficiency through employee delegation.
Keywords: employee participation; organisational performance; manufacturing sector; Nigeria.